Formação continuada de professores de matemática com enfoque colaborativo: contribuições para o uso reflexivo dos recursos da Web 2.0 na prática pedagógica - Sanavria, Claudio Zarate [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This thesis, part of the research line 2: Practices and Formative Processes in Education, aimed to investigate how the continuing teacher education with collaborative approach can contribute to a reflexive use of Web 2.0 resources for Mathematics Teachers. For the definition of the objectives, the following questions were established: how the Mathematics teachers are organized as a group, and how to go from a workgroup perspective to a group with collaborative features? What are the ideal characteristics of a continuing education for the use Web 2.0 features with collaboration as a guideline? How to perform a training that contributes to the effective use of technologies that aim to transform the practice? Within a qualitative descriptive-explanatory nature approach and intervening nature, we developed a continuing education with a group of Mathematics teachers in Nova Andradina - MS, which had the collaboration as a guideline, and through the data that emerged from it, we tried: 1) To analyze the composition of the group showing how mathematics teachers were organized in it, and identifying activities and knowledge that formed within this collaborative training process; 2) Identify and analyze the perceptions of mathematics teachers on the possibilities of use of Web 2.0 resources as a result of continuing education with collaborative approach; and 3) analyze the characteristics of the training process, identifying elements that contributed to the thoughtful use of Web 2.0 resources for Mathematics teachers. The training was organized in evolutionary cycles in which teachers, as a group, defined each of the resources to be exploited; they learned their features...

A presente tese, que se insere na Linha 2 - Práticas e Processos Formativos em Educação - teve como objetivo investigar como uma formação continuada com enfoque colaborativo pode contribuir para um uso reflexivo dos recursos da Web 2.0 por professores de Matemática. Para a definição dos objetivos estabelecemos as seguintes questões: Como os professores de Matemática se organizam enquanto grupo e como se passa de uma perspectiva de grupo de trabalho para a de um grupo com características colaborativas? Quais as características ideais de uma formação continuada para o uso recursos da Web 2.0 tendo a colaboração como eixo norteador? Como realizar uma formação que contribua para o uso das tecnologias de modo transformador em termos de práticas? Dentro de uma abordagem qualitativa de natureza descritivo-explicativa e com caráter interventivo, desenvolvemos com um grupo de professores de Matemática do município de Nova Andradina - MS uma formação continuada que teve a colaboração como eixo norteador e, por meio dos dados que nela emergiram, procuramos: 1) Analisar a constituição do grupo evidenciando como os professores de Matemática nele se organizaram e identificando fazeres e saberes que se constituíram dentro deste processo formativo colaborativo; 2) Identificar e analisar as percepções dos professores de Matemática sobre as possibilidades de uso dos recursos da Web 2.0 decorrentes da formação continuada com enfoque colaborativo; e 3) Analisar as características do processo formativo identificando elementos que contribuíram para o uso reflexivo dos recursos da Web 2.0 por professores de Matemática. A formação foi organizada em ciclos evolutivos nos quais os professores, em grupo, definiram cada um dos recursos a serem explorados, aprenderam as suas funcionalidades...
Keywords: Educação; Professores - Formação - Matemática; Educação permanente; Web 2.0; Education